There is No Anima Mundi: Leibniz on the Impossibility of a Soul of the World - Filippo Costantini (Ergo, An Open Access Journal of Philosophy, 2024)
The main source of perplexity raised by Leibniz’s (mathematical) argument against the soul of the world stems from the idea that it is the infinity of the universe that precludes it from having a soul. But if this is so, how is it possible that organic bodies, which, having infinitely many parts, are also infinite, are endowed with a soul? The present paper aims to provide a new solution to this puzzle. The solution explains the difference between the body and the universe by looking at how their respective parts are arranged. It is the arrangement of the parts of the body that allows a body to be divided into infinitely many parts whilst, at the same time, having a finite magnitude. By contrast, the way in which the alleged parts of the world are arranged makes it impossible that the world has a finite magnitude: the world cannot be a whole, and so it cannot have a soul. The consequence is that it does not matter how many parts bodies have, but only that they have a finite magnitude. In this case, bodies respect the Part-Whole Principle (the whole is bigger than any of its proper parts) and therefore can be described as finite wholes with parts.